Relationships between ventilatory impairment, sleep hypoventilation and type 2 respiratory failure - Hillman, D.; Singh, B.; McArdle, N.; Eastwood, Peter (Wiley-Blackwell Publishing Asia, 2014)
© 2014 Asian Pacific Society of Respirology. Conditions that increase load on respiratory muscles and/or reduce their capacity to cope with this load predispose to type 2 (hypercapnic) respiratory failure. In its milder forms, this imbalance between load and capacity may primarily manifest as sleep hypoventilation which, if untreated, can increase the likelihood of wakeful respiratory failure. Such problems are commonly seen in progressive respiratory neuromuscular disorders, morbid obesity and chronic obstructive pulmonary disease, either separately or together. Identifying patients at risk can be important in determining whether and when to intervene with treatments such as non-invasive ventilatory assistance. Measurements of wakeful respiratory function are fundamental to this risk assessment. These issues are reviewed in this paper.